X-3=3x+13

Simple and best practice solution for X-3=3x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-3=3x+13 equation:


Simplifying
X + -3 = 3x + 13

Reorder the terms:
-3 + X = 3x + 13

Reorder the terms:
-3 + X = 13 + 3x

Solving
-3 + X = 13 + 3x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + X = 13 + 3 + 3x

Combine like terms: -3 + 3 = 0
0 + X = 13 + 3 + 3x
X = 13 + 3 + 3x

Combine like terms: 13 + 3 = 16
X = 16 + 3x

Simplifying
X = 16 + 3x

See similar equations:

| -14+5v=-2(2-4v)-v | | -0.5a-0.666=0 | | 36+6n=6(3+4n) | | x-1/x-8 | | 5(x+1)-(4x-18)=11 | | -1.8-6z-1.5-z=-6z+1.2 | | http://media.education2020.com/evresources/646-10-05-00-00_files/i0110000.jpg | | .15*w=9 | | 36x^2+6x+1= | | 12/19x-1=3/5x | | 4-6(x-2)=-(2x+7) | | -25-3v=-5(v+3) | | 4x-8=4x-16 | | 6(v+4)-2v=2(2v+1)-3 | | 2+7(p-8)=-2(5p-7) | | -2(2x+5)-5x+4=-69 | | -4(4x-6)=24 | | 2b+3+1=8(2b+7)-8(b+5) | | 6x^2-19x=7 | | X=.40y-8 | | 10*(e^2n-10)-5=73 | | (x-1)/(x-8) | | 4+3(x-2)=3[4-6(x+3)] | | 2/3(x+4)=6 | | 10m+9=61 | | 3d+9=2d-7 | | 7x+1-2x=10+4x+2 | | 3/4t-6=3 | | 4[3x-4(5x+y)]=0 | | 6(x+4)-2x=2(2x+1)-3 | | x^0y^9= | | .06y+.1(10000-y)=.21y |

Equations solver categories